Supplementing ice core time series at Colle Gnifetti with a 3D full stokes ice flow model using Elmer/Ice - Licciulli, Carlo; Bohleber, Pascal; Wagenbach, Dietmar; Eisen, Olaf; Gagliardini, Olivier; Hoelzle, Martin (Platform Geosciences, Swiss Academy of Science, SCNAT, 2015)
The cold glacier saddle Colle Gnifetti (CG) is the unique drilling site in the European Alps offering ice core records substantially exceeding the instrumental period. However, the full exploitation of the unique potential of this site is hampered by depositional noise and, combined with a complex flow regime, upstream-effects. Here we present results from an ongoing new sophisticated flow modeling attempt, i.e. 3D full stokes with consideration of firn rheology, fully thermomechanically coupled, utilizing the finite element software Elmer/Ice. In view of our latest ice core drilled to bedrock in 2013, a major objective is to map source trajectories of existing ice core sites in order to evaluate potential upstream effects. An additional focus is to assist in finding a reliable age scale, especially targeting depths where annual layers can no more be counted. This includes the calculation of isochronous surfaces for intercomparison of different drilling sites within the CG multi core array. Previous numerical ice flow models of CG have been developed by W. Haeberli, S. Wagner, M. Lüthi (Lüthi & Funk 2000, 2001) and H. Konrad (Konrad et al. 2013). The level of accuracy of these previous works was mainly limited by the not well known bedrock topography and englacial temperatures. However, since the work of M. Lüthi several new temperature profiles are available (Hoelzle et al. 2011) and additional GPR measurements have been performed extensively (Bohleber 2011). Ongoing measurements will provide more precise information about the surface flow velocity, surface topography and their stationarity. In addition, two new ice cores have been drilled on CG, in 2005 and 2013. The 2013 drilling project employs a unique approach of combining multiple state-of-the-art methods in ice core analysis, for example new ultra-high resolution impurity analysis for detecting highly thinned annual layers as well as analysis of ice microstructure. All these new data sets together with the nowadays higher available computing power ...